High pretreatment static and dynamic alpha‐fetoprotein values predict reduced overall survival in hepatocellular carcinoma. Issue 3 (11th March 2021) - Czauderna, Carolin; Schmidtmann, Irene; Koch, Sandra; Pilz, Lukas; Heinrich, Sophia; Otto, Gerd; Mittler, Jens; Lang, Hauke; Kloeckner, Roman; Düber, Christoph; Sprinzl, Martin F.; Worns, Marcus A.; et al.
Abstract: Background: Hepatocellular carcinoma is one of the most lethal cancers worldwide. Novel prognostic and/or predictive biomarkers are urgently needed to improve patient management. Alpha‐fetoprotein (AFP) is a well‐established and widely used biomarker for hepatocellular carcinoma. However, diagnostic accuracy of static AFP values is limited and the clinical potential is a matter of ongoing scientific discussion. Objective: We here evaluated the prognostic impact of pretreatment static and dynamic AFP variables on overall survival of hepatocellular carcinoma patients in a Western cohort. Methods: Patients with confirmed hepatocellular carcinoma ( n = 809) treated at the Johannes Gutenberg University Mainz between 1998 and 2014 and two available pretreatment AFP‐values (AFP‐slope) were retrospectively analysed. Clinicopathological baseline parameters, pretreatment static values and AFP‐slope were assessed. Prognostic impact was determined by Kaplan–Meier analyses and Cox regression models. Results: High static and dynamic AFP variables prior to therapy were associated with reduced survival rates of hepatocellular carcinoma patients. Several known clinical parameters such as Child–Pugh B (p < 0.01) and C stage ( p < 0.001), portal vein thrombosis ( p < 0.001) and extrahepatic spread ( p < 0.001) were confirmed as independent predictors for overall survival. Addition of static and/or dynamic AFP variable resulted in higher time‐dependent area under the curves. Notably, in patients with more favourable prognosis, AFP‐slope prior to therapy was a slightly stronger predictor for overall survival compared with static AFP values. Conclusion: Static and dynamic AFP variables prior to therapy are predictive for overall survival of hepatocellular carcinoma patients. Addition of AFP‐slope to established prognostic parameters might improve prognostic classification for a subgroup of hepatocellular carcinoma patients with preserved liver function and without portal vein tumour thrombosis. Key Summary: Alpha‐fetoprotein (AFP) is the most commonly used biomarker for hepatocellular carcinomas (HCCs), but accuracy of static and dynamic AFP values is limited and the prognostic significance is under debate. High static and dynamic AFP variables prior to therapy are associated with reduced survival rates of HCC patients across different tumour stages and treatment modalities. In patients with more favourable prognosis, AFP‐slope prior to therapy was a better predictor for overall survival in comparison with static AFP values. Addition of AFP‐slope to established prognostic parameters might improve prognostic classification for a subgroup of HCC.